Privacy and Profitability in the Technological Workplace. - Nolan, Dennis R. (Journal of Labor Research)
Part of a special section on how new technologies influence the employment relationship. The writer discusses privacy and profitability in the technological workplace. He argues that new communications technology leads to new problems associated with privacy, and that each new technological development necessitates adjustments. He contends that differing responses to new communications technology are influenced by the perception that they offer privacy, and he concludes that employees and employers should seek to minimize the intrusions resulting from new technology, and that employers should resist the temptation to overreach.